Correlations of the global, regional and local factors of the anthropogenic effects on the water reserves of the Earth’s crust - Nagy, Sándor; Verdó, György (Acta Agraria Debreceniensis, 2012)
The decrease in Earth's drinking water resources and the degradation of its quality has become a critical problem. Our planet's total water supply is estimated to be around 2 billion km3s. This is only 1% of Earth's own weight. Of this small amount only a tiny 3% is fresh water, of which 79% is forzen in glaciers and 1% is present as surface waters.The ratio of water stored in soil is around 20%. This is 0.2% of the total water supply. Our study aims to summarize the layered groundwater aquifer systems and its changes which are the results of anthropogenic effects in both global and hungarian respects and also for the region of Debrecen.In particular with regard to the geological and ecological level where irreversibleprocesses take place. All this is discussed in the context of cause and effect. Pointing out the dangers of excessive deep groundwater extraction and the contamination caused by toxic substances that are the byproducts of modern life. In addition we discuss the Water Directive of the European Union which gives a policy for community action concerning the goal to achive the status of „in good condition” for our waters till 2015.